Uso do processo gama para dados de sobrevivência - Uêda, Shirley Tieko (2005)
In this dissertation, we introduce classical and Bayesian approaches to get inferences on the parameters of interest, considering exponential and Weibull distributions for the lifetimes. For a Bayesian analysis, we assume a gamma process for the individual rates considering type II censoring data and the presence of covariates. We also consider ac- celerated life tests assuming an inverse power law model and an exponential distribution for the lifetimes. The proposed methodology in illustrated in three examples.